2022
DOI: 10.3390/su14074171
|View full text |Cite
|
Sign up to set email alerts
|

A q-Rung Orthopair Fuzzy FUCOM Double Normalization-Based Multi-Aggregation Method for Healthcare Waste Treatment Method Selection

Abstract: Healthcare waste (HCW) management is an intricate issue upon which numerous factors, such as technical, economic, environmental, and social factors, have an impact. A determination on the best treatment method for HCW management can be viewed as a challenging multi-criteria decision-making (MCDM) problem in which various options and evaluation criteria are considered. One critical concern when assessing HCW treatment (HCWT) methods is the representation and treatment of dubious data. In this paper, we present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…To ensure that the best HCWTT can be selected under incomplete and uncertain information, EDAS applicable to the multi-granular linguistic environment [36] and generalized orthopair fuzzy environment [43] were proposed. To solve the HCWTT selection problem in q-rung orthopair fuzzy sets (QROFSs), Saha et al [44] suggested an MCDM method that used extended double normalization-based multi-aggregation (DNMA) to establish alternative ranking. Wang and Wang [45] used a Bonferroni mean operator to fuse linguistic information and designed an MCDM framework for HCWTT based on Combined Compromise Solution (CoCoSo).…”
Section: Evaluation and Decision Methods For Hcwtt Selectionmentioning
confidence: 99%
“…To ensure that the best HCWTT can be selected under incomplete and uncertain information, EDAS applicable to the multi-granular linguistic environment [36] and generalized orthopair fuzzy environment [43] were proposed. To solve the HCWTT selection problem in q-rung orthopair fuzzy sets (QROFSs), Saha et al [44] suggested an MCDM method that used extended double normalization-based multi-aggregation (DNMA) to establish alternative ranking. Wang and Wang [45] used a Bonferroni mean operator to fuse linguistic information and designed an MCDM framework for HCWTT based on Combined Compromise Solution (CoCoSo).…”
Section: Evaluation and Decision Methods For Hcwtt Selectionmentioning
confidence: 99%
“…Liang et al [19] constructed a novel tri-reference point (TRP) model for solving q-ROFS-based MCDM problem by considering the interaction of criteria with Bayesian network. Saha et al [20] presented the q-ROF-"full consistency method (FUCOM)"-"double normalization-based multi-aggregation (DNMA)" approach to deal with the "healthcare waste treatment technology (HCWTT)" assessment.…”
Section: A Fuzzy Sets For Multi-criteria Decision Makingmentioning
confidence: 99%
“…The technique that was most frequently used was DNMA (double-normalization-based multi-aggregation), which essentially makes use of double normalisation. With the help of the MCDM method with fuzzy information q-rung orthopair (q-ROFI), FUCOM (FUll COnsistency Method), and the DNMA method, Saha et al (2022) chose the best medical waste management strategies. Liao et al (2019) used the lung cancer-screening example to compare the effectiveness of the proposed models using the DNMA method and the fuzzy Delphi method.…”
Section: Literature Reviewmentioning
confidence: 99%